Hubungan Antara Pengetahuan, Pendapatan Ekonomi Dan Budaya Dengan Pernikahan Dini Pada Remaja Di Desa Sukaraja Kabupaten Bogor Tahun 2023 - Desi Arinia Rukiyah; Fitrya Ayu Anggraini; Indah Sri Wahyuni (Indonesian Journal of Midwifery Scientific, 2024)
The relationship between knowledge, economic income and culture and early marriage among teenagers in Sukaraja Village, Bogor Regency in 2023. Early marriage is a marriage between a man and a woman, both of whom are under the minimum age regulated by law. invite. According to the Child Protection Law, chapter 1, article 1 paragraph (1), what is meant by early age is someone who is not yet 18 (eighteen) years old. The above limitation confirms that children at an early age are part of adolescence. The aim of this research is to determine the factors related to the incidence of early marriage among teenagers in Sukaraja Village, Bogor Regency in 2023. This type of research is analytical descriptive with primary data. This research design uses "Cross Sectional". The sampling technique used in this research used a purposive sampling technique. Based on the results of the bivariate analysis, it can be seen that there is a significant influence between knowledge, economic income and culture and early marriage among teenagers in Sukaraja Village, Bogor Regency in 2023. There is a relationship between knowledge, economic income and culture and early marriage among teenagers in Sukaraja Village, Bogor Regency. In 2023. The community, especially teenagers, is expected to continue to increase knowledge about the impacts of early marriage to reduce and prevent the impacts caused by early marriage.